PKM Sosialisasi Gerakan Pemuda Membangun Desa Dalam Meningkatkanpendapatan Asli Desa - Lorita, Evi; Saputra, Harius Eko; Amin, Bando; Yusuarsono, Yusuarsono; Rikardo, Yanuar; Sulisman, Readi (Jurnal Dehasen Untuk Negeri, 2024)
A Community Service (PKM) activity with the theme "Socialization of the Youth Movement to Build Villages to Increase Village Original Income" was held in Rindu Hati Village, Taba Penanjung District, Central Bengkulu Regency. The main objective of this activity was to provide understanding and motivation to village youth to play an active role in development that has implications for increasing Village Original Income (PADes). The activity was carried out through direct socialization and counseling methods to youth and Karang Taruna administrators, by delivering material on youth, village development, and PADes management. The results of the activity showed that the participants were highly enthusiastic and gained a better understanding of the importance of the role of youth as agents of change, agents of development, and drivers of the local economy. This activity also encouraged the birth of creative and innovative ideas in developing village potential. Evaluation showed that this socialization was effective in increasing youth awareness and participation in sustainable development in Rindu Hati Village. The sustainability of the activity is expected through continued guidance and collaboration between the village government, educational institutions, and youth organizations.